Rancang Bangun Irigasi Tetes Emiter Tali untuk Budidaya Semangka (Citrullusvulgaris) - Muhammad Idrus; I Gde Darmaputra; Surya Surya (Jurusan Teknologi Pertanian, 2014)
The research was conducted at the Research Field of Lampung State Polytechnic, Bandar Lampung from August to November 2014. The objectives of the research ware: (1) to designing of the drip irrigation with plastic rope emitter for watermelon cultivation; (2) to determining the hydrolic criteria of the drip irrigation with plastic rope emitter for water melon cultivation; and (3 ) to testing the performanses of the drip irrigation with plastic rope emitter which are water storage efficiency, water distribution efficiency and water produktivity of water melon. The result of the research showed that the drip irrigation with plastic rope emitter with 2, 3, and 4 cm length of emitter given flow rate of 7.205, 6.40, and 2.790 l/s respectively on the operation pressure of 0,15 atm. The size of 1 sub block the drip irrigation with plastic rope emitter is 15 m x 50 m for minimize pressure variation in the sub block. The diameter and length of manifold pipe are 25 mm and 15 m, but the lateral pipe are 13 mm and 50 m. The diameter of main pipe depend on amount of the sub block irrigated on once time irrigation. Total dynamic head for two sub blocks irrigated is 3,44 m head and pump capacity minimal 1,02 l/s. The water storage efficiency, water distribution efficieny of the drip irrigation with plastic rope emitter were 100% and 87,73%. The water melon production on the the drip irrigation with plastic rope emitter was 5,83 kg/plant was not significant different compared to furrow irrigation method was 5,64 kg/plant. But irrigation water productivity of watermelon was significant different between of them. Water irrigation productivity of water melon by the drip irrigation with plastic rope emitter of 133 kg/plant was higher than the furrow irrigation method of 59 kg/plant. Amount of iririgation water application on water melon cultivation by the the drip irrigation with plastic rope emitter was only 44 l/plant, but the furrow irrigation method was higher of 96 l/plant. There for the amount of water irrigation can be conserved on water melon cultivation by the drip irrigation with plastic rope emitter was 54% compared to the furrow irrigation method. Keywords: drip irrigatoin, furrow irrigation, pressure operation emitter, flow rate, water melon, production, water storage efficieny, water distribution effiency, and irrigation water productivity.